Colon cancer with extensive invasion of the abdominal wall treated with neoadjuvant chemotherapy and a free anterolateral thigh flap - Tsukasa Aritake; Akira Ouchi; Koji Komori; Takashi Kinoshita; Yusuke Sato; Ryota Nakamura; Keisuke Takanari; Hiroya Taniguchi; Kei Muro; Seiichi Kato; Tetsuya Abe; Seiji Ito; et al. (Surgical Case Reports, 2022)
Abstract Background The treatment of locally advanced colon cancer is challenging, particularly when there is invasion of the abdominal wall. In such cases, balancing the securing of margins and sufficiently repairing abdominal wall defects is important, but difficult when the extent of invasion is large. Case presentation A 34-year-old male was referred to our hospital with abdominal pain and diagnosed with obstructive transverse colon cancer. He had undergone ileo-sigmoid colostomy at his previous hospital. The tumor was massive and invaded the abdominal wall (maximum diameter: approximately 12 cm), and was accompanied by regional lymph node swelling. No distant metastasis was detected. We diagnosed the tumor as cT4bN2bM0 Stage IIIC locally advanced transverse colon cancer and planned neoadjuvant chemotherapy. After two courses of FOLFOXIRI (5-fluorouracil, leucovorin, oxaliplatin, and irinotecan), he developed an entero-cutaneous fistula due to tumor penetration and required emergency diverting ileostomy construction. After the procedure, contrast-enhanced computed tomography showed good tumor shrinkage. As a result, the planned chemotherapy was canceled and he underwent radical resection of the tumor. En bloc extended right hemicolectomy was performed with excision of the fistula, ensuring a sufficient margin. The post-excision defect at the anterior abdominal wall involved 11 × 16 cm of fascia and 6 × 9 cm of skin located in the middle of the abdomen. A free anterolateral thigh flap was harvested from the right thigh and vascular pedicle was anastomosed to the right gastroepiploic artery and vein. The fascia lata, which was included in the anterolateral thigh flap, was sutured onto the abdominal wall fascia as inlay fashion to reconstruct the abdominal wall defect. Histopathology revealed moderately differentiated adenocarcinoma of the colon with no tumor cells in the abdominal wall tissue [post-chemotherapeutic state, therapy effect: Grade 1b; Stage IIA (ypT3N0M0)]. All resected margins of the specimen were free from adenocarcinoma. He was discharged on postoperative day 16. Conclusion We report a case of colon cancer extensively invading the abdominal wall, which was completely resected. The abdominal wall defect was reconstructed with a free anterolateral thigh flap after tumor shrinkage with neoadjuvant chemotherapy. We present an efficient strategy for managing locally advanced colon cancer with extensive abdominal wall invasion.